Modal sosial upaya peningkatan kinerja usaha kecil mikro keripik tempe sanan kota Malang - Fitrotun Nikmah; Farida Rahmawati (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
The purpose of this research is to identify the forms of application of social capital and the barriers to micro and small businesses of Sanan tempe chips in improving business performance for the sustainability of their business. Qualitative research used in this study. The data obtained in this study are qualitative data obtained through in-depth interviews, observation and documentation. The source of the data came from the informants of the UMK perpetrators of Malang's typical light meal, namely tempeh chips, Sanan as many as 8 people. Informants have joined this sector for at least 2 years as their main job. The results of the research analyzed that there is social capital owned by the tempe-sanan chip industry group in the form of trust, social networks, and norms. Trust and norms are the things that most influence MSEs, the existence of trust and norms with other business actors, and external parties such as customers, suppliers, and other communities. Business actors have a very good and wide social network to support their business activities. However, there are still various limitations and obstacles for actors both externally and internally.